Meta-analysis of community composition patterns of halophyte and xerophyte rhizosphere associated bacteria - Colchado-López, Joel; Rougon-Cardoso, Alejandra; Vélez, Patricia; Rosas, Ulises (Rhizosphere, 2022)
In plant roots, prokaryote-plant interactions have been extensively studied worldwide, demonstrating their importance for plant survival and growth, through the exploitation of microbial metabolic processes, such as nitrogen fixation and Extracellular Polymeric Substances (EPS). Climatic and edaphological forces structure the soil bacterial pool from which plants acquire a large share of their rhizosphere microbiome. As halophyte and xerophyte plants are subject to extreme environmental conditions, prokaryote-root interactions could be pivotal for plant establishment and survival, even more under the imminent scenario of climate change and increased water scarcity; yet, we have a limited understanding on large-scale geographical patterns of root-microbe communities in arid environments. Here, we used a meta-analysis approach to compare prokaryotic community composition associated to the rhizospheres of halophytes and xerophytes from ‘arid’ environments, representing 13 angiosperm plant species from five countries (Mexico, Namibia, Pakistan, Tunisia and USA), using a Qiime2 pipeline. In taxonomic terms, rhizosphere prokaryotic communities are diverse and include cosmopolitan classes like Alphaproteobacteria, Bacilli, and Gammaproteobacteria, as well as some site-specific groups like haline-thriving Haloarchaea, and PAUC43f which was found only in Pakistan samples. Alpha (ACE, Faith PD y Shannon) and beta (Jaccard) diversity estimates suggested that the main factors modeling microbial communities are host plant family, plant ecological strategy and the abiotic environment (bioclimatic variables, soil pH and total exchangeable bases). Furthermore, life history strategy (deciduous vs. perennial) is not significant for these communities' structure. Thus, this work presents an early sketch on the macro-geographical patterns driving rhizosphere microbiomes in arid environments. [Display omitted]